Land Suitability Analysis for Settlement Areas in Tilamuta District, Boalemo Regency - Nurzakiah, Siti Rahayu; Lihawa, Fitryane; Hasim, Hasim (Journal of Asian Multicultural Research for Social Sciences Study, 2022)
Tilamuta Subdistrict which is the capital of Boalemo Regency is directed as a Regional Activity Center (PKW) which has a function as a government center, urban settlement area, education area and trade and service area, but only about 35 percent of the total area of Tilamuta Subdistrict can be maximized as a function. built area. The purpose of this study was to determine the suitability of land for urban settlement areas in Tilamuta District. The analytical technique used is the overlay method using a Geographic Information System (GIS) from slope data, rainfall, morphology, soil type, land use and spatial pattern planning directions in Tilamuta District, which is then scored to determine the classification of land suitability of the area. settlement. The results showed that there were 4 land suitability classifications, namely: suitable (402 ha), quite suitable (4202 ha), less suitable (5223 ha), not suitable 8831 ha.